Proceedings of the 1st International Conference on Education Innovation (ICEI 2017) 2018
DOI: 10.2991/icei-17.2018.34
|View full text |Cite
|
Sign up to set email alerts
|

The effect of virtual labs toward students' understanding of physics based on gender

Abstract: The concept of physics consists of concrete and abstract concepts. Students should be able to master the concept of physics as well as to be able to solve problems in physics. Students' concept mastery can be improved by technology-based learning. The study was conducted at three different high schools. We investigated the students' mastery improvement in physics learning assisted by virtual lab media. The sample was chosen using purposive sampling resulting 34 male students and 36 female students. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
0
5
0
2
Order By: Relevance
“…In Zhao et al's study [68], a virtual laboratory was designed to support and enrich the undergraduate learners' laboratory experience in addition to the existing physical laboratory; the learners considered that the virtual laboratory was very informative and useful. Studies [69,70] revealed that the use of virtual laboratory media could improve the learners' conceptual understanding, as well as their problem-solving ability [71], and it enhances their creativity [72]. Jiménez et al's study [73] mentioned that virtual laboratories open new learning perspectives that cannot fully be explored in a traditional laboratory.…”
mentioning
confidence: 99%
“…In Zhao et al's study [68], a virtual laboratory was designed to support and enrich the undergraduate learners' laboratory experience in addition to the existing physical laboratory; the learners considered that the virtual laboratory was very informative and useful. Studies [69,70] revealed that the use of virtual laboratory media could improve the learners' conceptual understanding, as well as their problem-solving ability [71], and it enhances their creativity [72]. Jiménez et al's study [73] mentioned that virtual laboratories open new learning perspectives that cannot fully be explored in a traditional laboratory.…”
mentioning
confidence: 99%
“…The transition from on-campus lab to the virtual lab through E-learning has a significant influence on the E-learning outcomes in the engineering courses. Gunawan et al ( 2018 ) investigate the difference between student performances (cognitive skills) through virtual lab based on gender. Male students demonstrate higher scores than female students in higher-order cognitive skills (analyzing, creating, and forming).…”
Section: Literature Review Of Relevant Studiesmentioning
confidence: 99%
“…Some searches also yield precise solutions to specific problems in modern physics. According to Gunawan et al (2018), creativity is essential for understanding physics' abstract notions. The integration of information and communication technology in virtual laboratories is an example of innovation, which is why they set out to design a physics virtual laboratory that would enable effective learning for both male and female students.…”
Section: The Main Objectives Of the Research Studies On Using Interac...mentioning
confidence: 99%
“…Various research has identified the aspects that contribute to the success or failure of interactive simulations. Teachers must be cognitively capable of carrying knowledge to be utilized in their education and have the capacity and expertise to integrate new learning strategies in their classroom as one of the characteristics that promote success in the use of interactive simulation (Gunawan et al, 2018). Another crucial component is the teaching staff's expertise and abilities.…”
Section: Factors Aid Success or Failure In The Use Of Interactive Sim...mentioning
confidence: 99%